Técnicas de motivación y su influencia en el proceso de enseñanza y aprendizaje de los estudiantes de básica media de la escuela de educación básica “Tahuantinsuyo” parroquia san Cristóbal, cantón Quevedo - Ninasunta Oña, Mariela Aracely (2017)
This research has scientific foundations on bibliographic in fieldwork and research, an important part of scientific research involving psychology through motivation to improve the learning process through motivational techniques and their impact on the teaching and learning of the pupil. Basic Basic school education "Tahuantinsuyo" parish San Cristobal, Canton Quevedo, given the fact that school motivation coexists with many factors that are closely related to the learning environment in the classroom and these factors include: engaging students in activities that are emotional, successful and interested; rejecting your colleagues as a group; These factors are of great value, the teacher must strive to find the means to increase self-esteem, using observations to continue and reinforce each of their successes to inspire interest in learning; Teachers who study mathematics should consider these aspects in the teaching-learning process, so that it translates into changing students' attitudes towards it. Motivated students will have a particularly different interest in achieving their learning. To achieve the required motivation of students to their needs and expectations, and then directing behavior toward positive actions for students and their social context